ANATOMI DAN HISTOKIMIA ORGAN GENERATIF AMORPHOPHALLUS MUELLERI - Dwi Gusmalawati; Serafinah Indriyani; Rodiyati Azrianingsih (PTTI, 2013)
Porang is a tuber-producing plants and can be used as foodstuffs, cosmetics, pharmaceuticals and other industries. Porang growth cycle consists of vegetative phase and generative phase. The vegetative phase, when tuber produces petiole and lamina, while the generative phase, when tuber produces flower, fruit, and seeds. The aim of this study was to characterize the anatomy and histochemistry of porang generative organs. This research was conducted on the observations of anatomical characters, with the making of semi-permanent preparations and histochemical observations using fresh preparations. The results of the study showed that the surface of the adaxial and abaxial of the spathe structure of the epidermis was different, superior ovary, hemiantropus ovule, and bilobus anthers, each consisting of two loci. Porang fruit is a berry, thin pericarp with parenchymatous tissue that has a raphide sac and druse. Porang seed has thick testa and thin tegmen, as well as have the raphide sac. Based on testing of histochemistry, porang seeds contain starch, protein and lipid.